TIME RUNOFF WITH A TANK OUTLET TUBE: New calculation method - Armijo-Carranza, J. (1999)
We have developed a new calculation method to estimate the time delay in a liquid drain from a tank through a tube. The method uses the Newton iterative technique to calculate the velocity of the liquid and the flow rate in the tube, with an average deviation of 14 percent from the time of experimental drainage.